2018
DOI: 10.2147/cia.s170226
|View full text |Cite
|
Sign up to set email alerts
|

Possible predictive role of electrical risk score on transcatheter aortic valve replacement outcomes in older patients: preliminary data

Abstract: ObjectivesTo evaluate the predicative power of the electrical risk score (ERS), a noninvasive and inexpensive test obtained by means of a standard 12-lead electrocardiogram (ECG), in a cohort of elderly patients who had undergone transcatheter aortic valve replacement (TAVR).MethodsSurvivors and non-survivors after TAVR at 1-year follow-up were compared in respect to the pre-procedural ERS as well as a number of other clinical and instrumental variables. ERS is composed of seven simple ECG markers: heart rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…Furthermore, sympathetic over-activity, typical in chronic heart failure, could also play an important role as malignant ventricular arrhythmias’ trigger. In such a context, there are two previous observations corroborating these claims: it was recently confirmed that the sudden cardiac death during AS remains statistically important (Minamino-Muta et al, 2017) and, some non-invasive electrocardiographic (ECG) markers were found significantly associated to a poor outcome in elderly patients with AS after the transcatheter aortic valve replacement (TAVR) (Piccirillo et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, sympathetic over-activity, typical in chronic heart failure, could also play an important role as malignant ventricular arrhythmias’ trigger. In such a context, there are two previous observations corroborating these claims: it was recently confirmed that the sudden cardiac death during AS remains statistically important (Minamino-Muta et al, 2017) and, some non-invasive electrocardiographic (ECG) markers were found significantly associated to a poor outcome in elderly patients with AS after the transcatheter aortic valve replacement (TAVR) (Piccirillo et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
“…Indeed, in this last part of repolarization phase, I Ks is capable to modulate the QT duration to RR cycle length and, in chronic heart failure, these channels are downregulated. Thus, a mental stress could be sufficient to trigger this alteration also with conventional QT measurement (Aro et al, 2017; Tse et al, 2017; Piccirillo et al, 2018; Yu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Piccirillo et al 11 analyzed some electrocardiographic criteria to predict events and, among them, LV hypertrophy was correlated with general mortality (AUC, 0.76, p = .015). In our study, patients without hypertrophy, considered no confounders, had a higher mortality rate, despites this finding may look controversial, we believe this may be because these patients did not have an adaptive alteration at high ventricular postload and, therefore, had higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established a correlation between myocardial fibrosis and prognosis in AS 7‐10 . Imbalanced neuro‐autonomic control, ventricular hypertrophy, and the presence of fibrosis were strong predictors of both all‐cause and cardiovascular mortality in a group of elderly patients who underwent TAVR 11 …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation